Effect of Egyptian Leek Leaf Extract Supplementation on Productive and Economic Performance of Broilers - Al-khalaifah, Hanan S.; Badawi, Mohamed E.; Abd El-Aziz, Reda M.; Ali, Mohamed A.; Omar, Anaam E. (Frontiers in Veterinary Science, 2020)
Antibiotic growth promoters were used to improve growth and feed conversion for a large sum of time; they were banned due to several reported dangerous side effects on animals, poultry, and human. This work was carried out to investigate the effect of leek (Allium ampeloprasum var. kurrat) leaves extract (LLE) as non-traditional growth promoters and feed additive on growth performance, carcass characteristics, some serum biochemical parameters, and economic efficiency. Hubbard unsexed one-day-old broiler chicks (n = 250) were used and randomly assigned to one of five treatments with five replicates per treatment (50 chicks/ treatment; 10 chicks/replicate). The experimental chicks were fed with diets supplemented with 0 (control), 0.05, 0.1, 0.15 or 0.2% LLE for 42 days. Results revealed that LLE supplementation improved (P < 0.05) the different growth performance parameters. Furthermore, dietary LLE not only decreased the serum total cholesterol, triglyceride, low density lipoprotein (LDL) and glucose levels but also elevated serum high density lipoprotein level (HDL) as compared to control diet. Weight percentages of dressing and liver had a marked (P > 0.05) increase by the addition of LLE. Return, net profitand collective efficiency measures were increased (P = 0.000) in all LLE treatments in comparison with control treatment. Broilers fed diets contained 0.2% LLE showed the highest growth and economic efficiency. It could be concluded that supplementation with LLE in broiler chicken diets has a growth-promoting effect, improved the biochemical parameters and carcass quality, and promoted economic efficiency through maximizing both return and net profit.